2010
DOI: 10.1002/cncr.24999
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral forkhead box P3‐positive regulatory T cells predict poor survival in cyclooxygenase‐2–positive uveal melanoma

Abstract: BACKGROUND: Forkhead box P3 (FOXP3)-positive regulatory T cells (Tregs) are key mediators of peripheral tolerance and suppress efficient antitumor responses. Prostaglandin E 2 (PGE 2 ) produced by inducible cyclooxygenase-2 (COX-2) can lead to Treg induction. COX-2 expression has been linked to tumorigenesis and growth in various malignancies. The objective of the current study was to investigate whether Tregs infiltrate uveal melanomas (UMs) and whether their prevalence is linked to COX-2 expression and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
87
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 42 publications
2
87
0
Order By: Relevance
“…While UM cells possess tumor-associated antigens and tumor-infiltrating CD4 + and CD8 + cells are present in the primary UM, Treg cells are also present in the tumor. One study has identified that the frequency of CD4 + , forkhead box P3 (FoxP3) + Treg cells within primary UM is correlated with the development of systemic metastasis [10] . The presence of Treg cells and cyclooxygenase-2 expression in the tumors is especially correlated with poor prognosis [10] .…”
Section: Immunological Microenvironment Of Primary Uveal Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…While UM cells possess tumor-associated antigens and tumor-infiltrating CD4 + and CD8 + cells are present in the primary UM, Treg cells are also present in the tumor. One study has identified that the frequency of CD4 + , forkhead box P3 (FoxP3) + Treg cells within primary UM is correlated with the development of systemic metastasis [10] . The presence of Treg cells and cyclooxygenase-2 expression in the tumors is especially correlated with poor prognosis [10] .…”
Section: Immunological Microenvironment Of Primary Uveal Melanomamentioning
confidence: 99%
“…One study has identified that the frequency of CD4 + , forkhead box P3 (FoxP3) + Treg cells within primary UM is correlated with the development of systemic metastasis [10] . The presence of Treg cells and cyclooxygenase-2 expression in the tumors is especially correlated with poor prognosis [10] . In terms of the role of NK cells in primary UM, down-regulation of HLA class I, which is a common mechanism for evading CD8 + cells, renders tumors more susceptible to NK cell-mediated lysis.…”
Section: Immunological Microenvironment Of Primary Uveal Melanomamentioning
confidence: 99%
“…In many studies, Treg accumulation within tumours is a marker for poor clinical outcome. 37 When studying uveal melanoma, two studies found no association between Treg numbers in uveal melanoma and survival, 38,39 although the presence of Tregs has been associated with the extent of cyclooxygenase-2 expression, a bad prognostic factor. We do not yet know whether these cells are present in metastases and contribute to local immunosuppression in the liver.…”
Section: Suppression Of Immune Responsesmentioning
confidence: 99%
“…In the end, we reviewed 58 studies encompassing 16 different cancer types (Table 1), including bladder (19), breast (21)(22)(23)(24)(25)(26)(27)(28), cervical (29,30), colorectal (12,(31)(32)(33)(34)(35)(36)(37)(38)(39), endometrial (40)(41)(42), gastric (14,(43)(44)(45)(46), head and neck (47), hepatocellular (48)(49)(50)(51)(52), lung (53,54), melanoma (55)(56)(57)(58), mesothelial (59), oral (4,(60)(61)(62)(63), ovarian (2,3,…”
Section: Introductionmentioning
confidence: 99%